Synthesis and characterisation of mineral-derived and hybrid layered double hydroxides - Kwok, WLJ (2020)
This thesis discusses the development of atom efficient and scalable synthesis methods for the synthesis of industrially relevant layered double hydroxides (LDHs) using a green source of magnesium derived from a waste mineral. LDHs are introduced in Chapter 1 as compositionally flexible and versatile anionic clays. The structure of LDHs confers unique and interesting properties to these inorganic compounds and as such, LDHs have found application in a wide range of applications including environmental remediation and drug delivery. Naturally occurring LDHs are low in abundance but synthetic LDHs are facile to prepare and a variety of methods are available. The growing global demand for energy and resources calls for changes in the supply chain, so there is increasing interest in technologies and methods that are more environmentally friendly.